2006
DOI: 10.1128/aac.50.4.1282-1286.2006
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Analysis of IS Ecp1B -Mediated Mobilization of Naturally Occurring β-Lactamase Gene bla CTX-M of Kluyvera ascorbata

Abstract: ISEcp1B has been reported to be associated with and to mobilize the emerging expanded-spectrum ␤-lactamase bla CTX-M genes in Enterobacteriaceae. Thus, the ability of this insertion sequence to mobilize the bla CTX-M-2 gene was tested from its progenitor, Kluyvera ascorbata. Insertions of ISEcp1B upstream of the bla CTX-M-2 gene in K. ascorbata reference strain CIP7953 were first selected with cefotaxime (0.5 and 2 g/ml). In those cases, ISEcp1B brought promoter sequences enhancing bla CTX-M-2 expression in K.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
130
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(137 citation statements)
references
References 33 publications
(53 reference statements)
5
130
0
2
Order By: Relevance
“…boring genes by one-ended transposition mechanism. A recent in vitro study showed that the mobilization of bla CTX-M-2 from K. ascorbata to E. coli was achievable in the presence of ISEcp1 [45]. Genes encoding the CTX-M-2 subgroup and the CTX-M-9 subgroup have also been observed within ISCR1 associated with class 1 integron.…”
Section: Ctx-mmentioning
confidence: 99%
“…boring genes by one-ended transposition mechanism. A recent in vitro study showed that the mobilization of bla CTX-M-2 from K. ascorbata to E. coli was achievable in the presence of ISEcp1 [45]. Genes encoding the CTX-M-2 subgroup and the CTX-M-9 subgroup have also been observed within ISCR1 associated with class 1 integron.…”
Section: Ctx-mmentioning
confidence: 99%
“…Selection was performed on gentamicin (8 g/ml)-, kanamycin (30 g/ ml)-, and amoxicillin (50 g/ml)-containing plates. E. coli RZ211 was then used as a donor for mating-out assays with E. coli J53 Azide r , with selection on gentamicin (8 g/ml) and azide (100 g/ml) with or without amoxicillin (50 g/ml)-containing plates, as described previously (14,22). The transposition frequency was calculated by dividing the number of Gen r Amx r Azide r transconjugants by the number of Gen r Azide r transconjugants.…”
mentioning
confidence: 99%
“…3 The movement of transposons, such as ISEcp1B, may promote resistance to gene evolution. 14,15 The identification of a new CTX-M ESBLs gene subtype, the ISEcp1B/IS903 hybrid, which is a composite of known insertion sequences is evidence that evolution is occurring during these horizontal transfers. Similar composite transposons consisting of ISEcp1B and IS903 flanking the CTX-M-1, CTX-M-9, CTX-M-15, CTX-M-17 and CTX-M-54 genes, were reported in Europe, the Americas and Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Similar composite transposons consisting of ISEcp1B and IS903 flanking the CTX-M-1, CTX-M-9, CTX-M-15, CTX-M-17 and CTX-M-54 genes, were reported in Europe, the Americas and Asia. 7,10,14 We previously participated in a drug resistance monitoring group organized by the 13 major hospitals in the Guangzhou region from July 2001 to August 2003 and obtained 3500 strains of non-repetitive continuous isolates of Gram-negative bacilli. Of these 31% (1084 of 3500) were positive for the ESBL phenotype.…”
Section: Discussionmentioning
confidence: 99%